Efektivitas E-Modul Berbasis Guided Discovery Learning (GDL) pada Materi Asam dan Basa terhadap Hasil Belajar Kognitif Siswa SMA Fase F - Nur Asdeanti; Yerimadesi Yerimadesi (MASALIQ, 2026)
Acids and Bases is one of the chemistry topics that consistently causes difficulties for students, especially in integrating the three levels of chemical representation, so more interactive and structured learning media are needed. This study aims to determine the effectiveness of a Guided Discovery Learning (GDL)-based e-module on the cognitive learning outcomes of Phase F senior high school students in the topic of Acids and Bases. This study employed a quantitative approach with a quasi-experimental Nonequivalent Control Group Design, involving 27 students in the experimental class and 31 students in the control class at SMA Pembangunan Laboratorium UNP in the even semester of the 2025/2026 academic year. Data were collected using 15 multiple-choice items (α = 0.958) and analyzed using N-Gain, the normality test, the homogeneity test, and the independent t-test. The results showed a significant difference in cognitive learning outcomes between the two classes (sig < 0.05), with the mean score of the experimental class increasing from 67 to 83.41, whereas the control class increased from 36 to 49. The N-Gain value of the experimental class was 0.5163, which was higher than that of the control class at 0.4674, although both were in the moderate category. These findings indicate that the GDL-based e-module is effective in improving students’ cognitive learning outcomes in the topic of Acids and Bases. Thus, this study contributes to the development of digital-based chemistry learning and recommends the wider implementation of GDL-based e-modules in schools with adequate digital infrastructure.